Runx2 is essential for the transdifferentiation of chondrocytes into osteoblasts - Qin, Xin; Jiang, Qing; Nagano, Kenichi; Moriishi, Takeshi; Miyazaki, Toshihiro; Komori, Hisato; Ito, Kosei; von der Mark, Klaus; Sakane, Chiharu; Kaneko, Hitomi; Komori, Toshihisa (PLoS Genetics, 2020)
Chondrocytes proliferate and mature into hypertrophic chondrocytes. Vascular invasion into the cartilage occurs in the terminal hypertrophic chondrocyte layer, and terminal hypertrophic chondrocytes die by apoptosis or transdifferentiate into osteoblasts. Runx2 is essential for osteoblast differentiation and chondrocyte maturation. Runx2-deficient mice are composed of cartilaginous skeletons and lack the vascular invasion into the cartilage. However, the requirement of Runx2 in the vascular invasion into the cartilage, mechanism of chondrocyte transdifferentiation to osteoblasts, and its significance in bone development remain to be elucidated. To investigate these points, we generated Runx2fl/flCre mice, in which Runx2 was deleted in hypertrophic chondrocytes using Col10a1 Cre. Vascular invasion into the cartilage was similarly observed in Runx2fl/fl and Runx2fl/flCre mice. Vegfa expression was reduced in the terminal hypertrophic chondrocytes in Runx2fl/flCre mice, but Vegfa was strongly expressed in osteoblasts in the bone collar, suggesting that Vegfa expression in bone collar osteoblasts is sufficient for vascular invasion into the cartilage. The apoptosis of terminal hypertrophic chondrocytes was increased and their transdifferentiation was interrupted in Runx2fl/flCre mice, leading to lack of primary spongiosa and osteoblasts in the region at E16.5. The osteoblasts appeared in this region at E17.5 in the absence of transdifferentiation, and the number of osteoblasts and the formation of primary spongiosa, but not secondary spongiosa, reached to levels similar those in Runx2fl/fl mice at birth. The bone structure and volume and all bone histomophometric parameters were similar between Runx2fl/fl and Runx2fl/flCre mice after 6 weeks of age. These findings indicate that Runx2 expression in terminal hypertrophic chondrocytes is not required for vascular invasion into the cartilage, but is for their survival and transdifferentiation into osteoblasts, and that the transdifferentiation is necessary for trabecular bone formation in embryonic and neonatal stages, but not for acquiring normal bone structure and volume in young and adult mice.
CRIS-Team Scopus Importer:2020-12-11